Delayed insulin absorption correlates with alterations in subcutaneous depot kinetics in rats with diet‐induced obesity - A. K. J. Gradel; T. Porsgaard; P. B. Brockhoff; T. Seested; J. Lykkesfeldt; H. H. F. Refsgaard (Wiley, 2019)
Summary Objective Obesity is associated with delayed insulin absorption upon subcutaneous (s.c.) dosing in humans. The aim of this study was to investigate whether alterations in depot structure and kinetics of the s.c. injection depot contribute to this delay. Methods Rats fed a high‐fat diet (HFD) and low‐fat diet (LFD) were included in a series of insulin pharmacokinetic and imaging studies. Injection depots were visualized with micro X‐ray computed tomography imaging upon s.c. administration of insulin aspart mixed with the contrast agent iomeprol, and insulin aspart exposure was measured by means of luminescent oxygen channelling immunoassay. Results Body weight and fat mass were increased in rats fed an HFD vs. LFD (p < 0.05), whereas the lean mass was not. The HFD group exhibited delayed insulin absorption from the s.c. tissue (p < 0.001). This delay was associated with smaller injection depots upon s.c. dosing (p < 0.05) and correlated with a slower depot disappearance from the s.c. tissue (p < 0.05) compared with the LFD group. Depot disappearance from the s.c. tissue was inversely correlated with body fat mass (p < 0.05). Conclusions Alterations in s.c. injection depot structure and kinetics may play a role in the obesity‐associated delay in insulin absorption.